2004
DOI: 10.1111/j.1600-6143.2004.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil Can Be Used as Monotherapy Late After Liver Transplantation

Abstract: We report our experience with calcineurin inhibitor (CNI) withdrawal and MMF monotherapy in 50 adult liver transplant (OLT) recipients with CNI-related toxicity. Thirty-four patients had chronic renal dysfunction (CRD) associated with arterial hypertension, 11 had only CRD and other five patients had hypertension. The mean time between OLT and introduction of MMF was 81 months. After the introduction of MMF, CNI was progressively reduced and withdrawn if possible. At the end of the follow up (mean time: 18 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 21 publications
3
26
0
1
Order By: Relevance
“…The incidence of acute rejection was lower in patients treated with MMF, but patient and graft survival rates were similar at 1 year. In addition to replacing azathioprine as part of a triple therapy regimen after liver transplantation, MMF may also have a role in permitting CNI dose reduction or withdrawal in recipients with renal dysfunction [80][81][82], although such a strategy is not completely without risk [81].…”
Section: Mmf In Liver Transplantationmentioning
confidence: 98%
“…The incidence of acute rejection was lower in patients treated with MMF, but patient and graft survival rates were similar at 1 year. In addition to replacing azathioprine as part of a triple therapy regimen after liver transplantation, MMF may also have a role in permitting CNI dose reduction or withdrawal in recipients with renal dysfunction [80][81][82], although such a strategy is not completely without risk [81].…”
Section: Mmf In Liver Transplantationmentioning
confidence: 98%
“…Most studies showed improvement in renal function, but recovery was more pronounced when CNI were totally withdrawn (6,7). To improve management of patients with CNI-induced severe side effects, complete CNI withdrawal which was then followed by MMF monotherapy had been previously evaluated in small-cohort-size studies, which reported an average 15% risk of acute rejection (6,(8)(9)(10)(11)(12)(13)(14)(15). Therefore, complete replacement of CNI followed by MMF monotherapy remains highly controversial (9,15 Figure 1.…”
Section: The Classical Immunosuppressive Regimen Widely Used After LImentioning
confidence: 99%
“…25 More recent studies focusing on patients with CNI-related side effects (renal dysfunction and metabolic side effects in particular) over the long term have been more promising. [26][27][28][29] In these series, MMF monotherapy was most often considered more than 1 year after transplantation. In all cases, MMF was introduced, and in parallel, CNIs were slowly tapered for discontinuation within 4 to 6 months.…”
Section: Cni Withdrawal and Mmf Monotherapymentioning
confidence: 99%
“…26 In these select patients, the rate of acute rejection was low (<10%). 29 Chronic rejection was a rare event, and CNIs had to be reintroduced in only a few patients. 28 However, because of the potential risk of rejection and graft loss, physicians should be very cautious with CNI withdrawal and MMF monotherapy and should closely monitor liver function tests.…”
Section: Cni Withdrawal and Mmf Monotherapymentioning
confidence: 99%